Can serum periostin, YKL‐40, and osteopontin levels in pre‐school children with recurrent wheezing predict later development of asthma?. Issue 1 (9th September 2020) - Guvenir, Hakan; Buyuktiryaki, Betul; Kulhas Celik, Ilknur; Civelek, Ersoy; Kilic Suloglu, Aysun; Karaaslan, Cagatay; Genc, Selcan; Dibek Misirlioglu, Emine; Toyran, Muge; Ginis, Tayfur; Kocabas, Can N.
Abstract: Background: Currently, there are no reliable clinical tools available for predicting asthma in pre–school‐aged children with recurrent wheezing. The aim of this study was to evaluate the usefulness of serum periostin, YKL‐40, and osteopontin biomarkers in wheezy pre–school‐aged children for predicting the development of asthma in school ages. Methods: The study was prospectively conducted between 2011 and 2017. The clinical features of the pre–school‐aged children with recurrent wheezing and the levels of serum periostin, YKL‐40, and osteopontin were measured. The same participants were reevaluated in school‐age period, and participants with asthma were identified. Relative risk (RR) for the development of asthma was analyzed. Results: Of the 197 pre–school‐aged children with recurrent wheezing who were reevaluated in school‐age years, 32% of them had asthma. Serum periostin, YKL‐40, and osteopontin levels at admission could not predict participants who would have asthma symptoms in school‐age years. The RR for continuing of asthma symptoms was higher in participants who had their first wheezing episode before 1 year of age, preterm birth, cesarean section delivery, prenatal smoking exposure, multi‐trigger wheezing, parental asthma, modified asthma predictive index positivity, prophylactic vitamin D intake ≤ 12 months, breastfeeding time ≤ 12 month, and aeroallergen sensitivity [RR (95% CI) and P value: 2.813 (1.299‐6.091), 0.002; 1.972 (1.274‐3.052), 0.009; 1.929 (1.195‐3.114), 0.004; 2.232 (1.463‐3.406), <0.001; 3.152 (1.949‐5.097), <0.001; 1.730 (1.144‐2.615), 0.016; 2.427 (1.559‐3.777), <0.001; 2.955 (1.558‐5.604), <0.001; 1.767 (1.084‐2.881), 0.016; 0.765 (0.556‐1.053), 0.016; respectively]. Conclusion: Results have shown that clinical features were more valuable than biomarkers in predicting having asthma in school‐age years in participants who had recurrent wheezing in pre–school‐age period.